Analisis Tata Kelola Tanah Kas Desa dalam Meningkatkan Pendapatan Asli Desa (Padesa) di Desa Lebo, Kecamatan Sidoarjo, Kabupaten Sidoarjo - Azwara Izzamar Rofie; Deby Febriyan Eprilianto; Galih Wahyu Pradana; Revienda Anita Fitrie (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the governance of Village Treasury Land (Tanah Kas Desa/TKD) covering an area of approximately 19 hectares in increasing Village Original Income (Pendapatan Asli Desa/PADesa) in Lebo Village, Sidoarjo District, Sidoarjo Regency. The analytical framework is based on nine good governance principles according to Mardiasmo (2018): accountability, transparency, participation, rule of law, responsiveness, efficiency and effectiveness, consensus orientation, equity, and strategic vision. This study adopts a descriptive qualitative approach with a case study method. Data collection was conducted through in-depth interviews with village government officials, the Village BPD, tenants, and community members, alongside field observations and documentation. The findings indicate that TKD governance in Lebo Village remains dominated by conventional agricultural and commercial leasing schemes. The implementation of good governance principles is not yet optimal, as evidenced by limited transparency and public participation due to leasing mechanisms lacking open bidding. In terms of economic contribution, the growth rate of Lebo Village's PADesa shows a decelerating trend with potential stagnation, reflecting sub-optimal execution of efficiency, effectiveness, and strategic vision in diversifying productive land use. Therefore, a transformation in TKD management policy toward a more transparent, participatory, and innovative model is necessary to maximize village fiscal independence and enhance community welfare.